Negative electrode for lithium secondary battery, method for manufacturing negative electrode for lithium secondary battery, and lithium secondary battery including negative electrode
By adopting a double-layer active material layer structure in the negative electrode of the lithium secondary battery, and using high-content SiOx and carbon-based silicon-based active materials, the problems of reducing capacity characteristics of silicon-based compounds in the lithium secondary battery and deteriorating electrode surface in the lithium secondary battery are solved, and efficient activation steps and excellent cycling performance are achieved.
Patent Information
- Application Number
- CN202380056561.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-26
- Filing Date
- 2023-12-26
- Publication Date
- 2025-03-11
AI Technical Summary
When using a silicon-based compound as the negative electrode active material of lithium secondary battery, there are problems such as decreasing capacity characteristics, deterioration of electrode surface during charge and discharge cycles, and prolonging of activation process time.
A two-layer active material layer structure is adopted, wherein the first negative electrode active material layer consists of a high content of SiOx, and the second negative electrode active material layer includes a carbon system and a silicon system active material. By adjusting the activation process conditions, the optimal arrangement of the silicon phase is ensured.
When using silicon-based active materials, it is achieved to maximize capacity characteristics, prevent electrode surface deterioration, shorten activation process time, and ensure the optimal arrangement of the silicon phase, which improves the circulation performance and life of the lithium secondary battery.
Smart Images

Figure CN119604985A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0184204 filed in the Korean Intellectual Property Office on December 26, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for manufacturing the negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. Background Art
[0003] As a part of the increasing demand for the use of alternative or clean energy due to the rapid increase in the use of fossil fuels, the most active research field is the field of power generation and storage using electrochemical reactions.
[0004] Currently, secondary batteries are a representative example of electrochemical devices utilizing such electrochemical energy, and the scope of use thereof tends to be gradually expanded.
[0005] As the technology development and demand for mobile devices increase, the demand for secondary batteries as energy sources has increased dramatically. Among such secondary batteries, lithium secondary batteries with high energy density and voltage, long cycle life and low self-discharge rate have been commercialized and widely used. In addition, as electrodes for such high-capacity lithium secondary batteries, the manufacturing method of high-density electrodes with higher energy density per unit volume is being actively studied.
[0006] Generally, a secondary battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material for inserting and extracting lithium ions from the positive electrode, and silicon-based particles having a high discharge capacity can be used as the negative electrode active material.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, a method of increasing capacity by using a silicon-based compound such as Si / C or SiOx as a negative electrode active material in combination with a capacity as high as 10 times or more of the capacity of a graphite-based material is being actively studied. However, when compared with the commonly used graphite, the silicon-based compound as a high-capacity material is excellent in capacity characteristics itself, but the volume expands rapidly during charging, thereby disconnecting the conductive path, causing the battery characteristics to deteriorate, and therefore, the capacity is reduced from the initial stage. In addition, for silicon-based negative electrodes, when the charge and discharge cycle is repeated, the lithium ions are not uniformly charged in the depth direction of the negative electrode and the reaction proceeds on the surface, which accelerates the surface degradation, and therefore, it is necessary to improve the performance in terms of battery cycle.
[0008] Therefore, in order to solve the problems that arise when using silicon-based compounds as negative electrode active materials, various methods have been discussed, such as a method of controlling the driving potential, a method of additionally coating a thin film on the active material layer, a method of suppressing the volume expansion itself such as a method of controlling the particle size of the silicon-based compound, or developing a binder that can suppress the volume expansion of the silicon-based compound to prevent disconnection of the conductive path. In addition, research has been conducted on limiting the usage ratio of the silicon-based active material during the initial charge and discharge and imparting a storage effect by pre-lithiating the silicon-based active material layer to supplement the life characteristics of the silicon-based negative electrode.
[0009] However, since the above method may deteriorate the performance of the battery, it is limited in application, and thus there are still limitations in the commercialization of the manufacture of negative electrode batteries with a high silicon compound content. In addition, as the ratio of the silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, so that the silicon-based active material on the surface is damaged, and due to the occurrence of uneven pre-lithiation, there are problems in improving the life characteristics.
[0010] Furthermore, the silicon-based negative electrode undergoes a charge and discharge cycle during the activation process, at which time it cannot be charged at a high rate due to the influence of the highly reactive silicon-based active material, which increases the time of the activation process and causes problems in the manufacturing process.
[0011] Therefore, it is necessary to study a negative electrode that does not cause a decrease in capacity characteristics even when a silicon-based compound is used as an active material to improve capacity characteristics, can improve cycle performance by preventing electrode surface degradation during charge and discharge cycles, can shorten the process time during the activation process, and cause optimal silicon phase arrangement due to the activation process.
[0012] Prior art literature
[0013] (Patent Document 1) Japanese Patent Application Publication No. 2009-080971 Summary of the invention
[0014] Technical issues
[0015] The present application relates to a negative electrode for a lithium secondary battery, a method for manufacturing a negative electrode for a lithium secondary battery, and a lithium secondary battery comprising the negative electrode. While using a silicon-based active material for the negative electrode, the negative electrode is capable of: maximizing capacity characteristics (which is the main purpose of using the silicon-based active material); preventing electrode surface degradation during charge and discharge cycles (which is a problem in the related art); and achieving optimal arrangement of silicon phases in the negative electrode active material layer through a high-rate activation process.
[0016] That is, the main feature of the negative electrode for a lithium secondary battery according to the present application lies in defining the state of the silicon phase in the negative electrode for a lithium secondary battery that can exhibit a capacity retention rate and resistance characteristics equal to or higher than those of a negative electrode with an increased process time by applying a low-rate activation process, and ensuring processability.
[0017] Technical solution
[0018] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode comprising: a negative electrode current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer comprises a first negative electrode active material layer provided on the negative electrode current collector layer and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to the surface facing the negative electrode current collector layer, wherein the first negative electrode active material layer comprises a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer comprises a second negative electrode active material layer composition containing a second negative electrode active material, wherein the first negative electrode active material comprises one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more relative to 100 parts by weight of the first negative electrode active material, wherein the second negative electrode active material comprises one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium nitride-containing material, wherein the ratio of amorphous silicon contained in the first negative electrode active material layer is lower than the ratio of amorphous silicon contained in the second negative electrode active material layer, and wherein the ratio of the silicon phase contained in the negative electrode active material layer satisfies the following formula 1:
[0019] [Formula 1]
[0020] 5 ≤ B / (A + B)×100(%) ≤ 30
[0021] In formula 1, A refers to the parts by weight of the crystalline phase relative to 100 parts by weight of the silicon phase contained in the negative electrode active material layer, and B refers to the parts by weight of the amorphous phase relative to 100 parts by weight of the silicon phase contained in the negative electrode active material layer.
[0022] Another exemplary embodiment provides a lithium secondary battery, the lithium secondary battery comprising: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
[0023] In addition, a method of manufacturing a lithium secondary battery is provided, the method comprising: preparing a lithium secondary battery including a positive electrode, a negative electrode for a lithium secondary battery, a separator, and an electrolyte; and activating the lithium secondary battery, wherein the activation includes a high C-rate activation process (high-rate charging), wherein preparing the negative electrode for a lithium secondary battery includes: preparing a negative electrode current collector layer, forming a first negative electrode active material layer by applying a first negative electrode active material layer composition to one surface or both surfaces of the negative electrode current collector layer using a coater, and forming a second negative electrode active material layer by applying a second negative electrode active material layer composition to the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer using a coater, wherein the first negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more with respect to 100 parts by weight of the first negative electrode active material, and wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0024] Advantageous Effects
[0025] The negative electrode for a lithium secondary battery according to an exemplary embodiment of the present invention has a double-layer active material layer composed of the first negative electrode active material layer and the second negative electrode active material layer. In particular, the first negative electrode active material included in the first negative electrode active material layer includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), the content of SiOx (x = 0) is 95 parts by weight or more with respect to 100 parts by weight of the first negative electrode active material, and the second negative electrode active material included in the second negative electrode active material layer includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0026] The negative electrode for a lithium secondary battery according to the present application includes a double-layer active material layer having the specific composition and content as described above. In particular, the first negative electrode active material layer includes a high content of SiOx (x = 0), so that the advantages of high capacity, high density, and fast charging can be maintained as they are. In addition, a silicon-based active material and / or a carbon-based active material, etc. are included in the second negative electrode active material layer, so that deterioration of the electrode surface during charge and discharge cycles can be prevented, and uniformity during prelithiation can also be improved.
[0027] Among them, in particular, the negative electrode for a lithium secondary battery according to the present application can achieve high C-rate charging during the activation process, thereby achieving an optimal arrangement of the silicon phase in the negative electrode active material layer, so as to satisfy the range of the above formula 1.
[0028] Therefore, a lithium secondary battery including the negative electrode satisfies the optimum capacity characteristics, which is an advantage of the Si negative electrode, while satisfying the cycle characteristics.
[0029] As a result, in order to give full play to the advantages of using high-content Si particles as single-layer active material electrodes, and to solve the disadvantages caused by the application of high-content Si particles, such as surface degradation problems, uniformity problems during pre-lithiation, and life characteristics problems, according to the negative electrode for lithium secondary batteries of the present application, the second negative electrode active material layer is coated on the upper part of the first negative electrode active material layer, and at the same time, by adjusting the conditions of the activation process, the optimal arrangement of the silicon phase in the negative electrode active material layer (especially the arrangement of the silicon phase in the first negative electrode active material layer) is achieved, thereby satisfying the range of the above formula 1. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0031] Figure 2 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application.
[0032] Figure 3 is a flow chart showing a wet-on-dry process according to an exemplary embodiment of the present application.
[0033] Figure 4 is a flow chart showing a wet-on-wet process according to an exemplary embodiment of the present application.
[0034] Figure 5 : is a graph showing silicon phase distribution obtained by Raman analysis of the negative electrodes (first negative electrode active material layer) for lithium secondary batteries according to Examples 1 to 4 of the present application.
[0035] Figure 6 : is a graph showing silicon phase distribution obtained by Raman analysis of the negative electrodes (first negative electrode active material layer) for lithium secondary batteries according to Comparative Examples 1 to 4 of the present application.
[0036] Figure 7 This is a SEM photograph of a cross section of a negative electrode for a lithium secondary battery according to Comparative Example 5 of the present application.
[0037] <Description of symbols>
[0038] 10: Second negative electrode active material layer
[0039] 20: First negative electrode active material layer
[0040] 30: Negative electrode collector layer DETAILED DESCRIPTION
[0041] Before describing the present invention, some terms are first defined.
[0042] In the present specification, when a part “includes,” “contains,” or “has” a constituent element, unless otherwise specifically stated, this does not mean that other constituent elements are excluded but that other constituent elements may be further included.
[0043] In this specification, "p to q" means a range of "p or more and q or less".
[0044] In this specification, "specific surface area" is measured by the BET method, specifically, calculated from the nitrogen adsorption amount at liquid nitrogen temperature (77 K) using BELSORP-mini II available from BEL Japan, Inc. That is, in this application, the BET specific surface area may refer to the specific surface area measured by the above-mentioned measurement method.
[0045] In this specification, "Dn" refers to particle size distribution, and refers to the particle size at n% point in the cumulative distribution of particle number according to particle size. That is, D50 is the particle size (average particle size, center particle size) at 50% point in the cumulative distribution of particle number according to particle size, D90 is the particle size at 90% point in the cumulative distribution of particle number according to particle size, and D10 is the particle size at 10% point in the cumulative distribution of particle number according to particle size. On the other hand, the particle size distribution can be measured using a laser diffraction method. Specifically, after the powder to be measured is dispersed in a dispersion medium, the resulting dispersion is introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), wherein the difference in diffraction patterns according to particle size is measured when the laser beam passes through the particle, and then the particle size distribution is calculated.
[0046] In the present specification, the description "a polymer includes a certain monomer as a monomer unit" means that the monomer participates in the polymerization reaction and is included in the polymer as a repeating unit. In the present specification, when a polymer includes a monomer, this should be interpreted as the same as the polymer including the monomer as a monomer unit.
[0047] In this specification, unless otherwise indicated as a "homopolymer", the term "polymer" is understood to be used in a broad sense including copolymers.
[0048] In this specification, the weight average molecular weight (Mw) and the number average molecular weight (Mn) are polystyrene-converted molecular weights measured by gel permeation chromatography (GPC) while using commercially available monodisperse polystyrene polymers (standard samples) with different polymerization degrees for measuring molecular weight as standard materials. In this specification, unless otherwise specifically stated, molecular weight refers to weight average molecular weight.
[0049] Embodiments of the present invention will be described in detail below with reference to the accompanying drawings, so that those skilled in the art can easily implement the present invention. However, the present invention can be implemented in various different forms and is not limited to the following description.
[0050] An exemplary embodiment of the present specification provides a negative electrode for a lithium secondary battery, the negative electrode including: a negative electrode current collector layer; and a negative electrode active material layer provided on one surface or both surfaces of the negative electrode current collector layer, wherein the negative electrode active material layer includes a first negative electrode active material layer provided on the negative electrode current collector layer and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to the surface facing the negative electrode current collector layer, wherein the first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, wherein the first negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more relative to 100 parts by weight of the first negative electrode active material, wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium nitride-containing material, wherein the ratio of amorphous silicon contained in the first negative electrode active material layer is lower than the ratio of amorphous silicon contained in the second negative electrode active material layer, and wherein the ratio of the silicon phase contained in the negative electrode active material layer satisfies the following formula 1:
[0051] [Formula 1]
[0052] 5 ≤ B / (A + B)×100(%) ≤ 30
[0053] In Formula 1, A refers to the weight part of the crystalline phase relative to 100 weight parts of the silicon phase contained in the negative electrode active material layer, and B refers to the weight part of the amorphous phase relative to 100 weight parts of the silicon phase contained in the negative electrode active material layer.
[0054] In order to exert the advantages of an electrode using a high content of Si particles as a single-layer active material and to solve the disadvantages caused when using a high content of Si particles, such as surface deterioration problems, uniformity problems during prelithiation, and life characteristic problems, the negative electrode for a lithium secondary battery according to the present application coats the second negative electrode active material layer on the upper part of the first negative electrode active material layer. At the same time, by adjusting the conditions of the activation process, an optimal arrangement of the silicon phase in the negative electrode active material layer is achieved, thereby satisfying the range of the above formula 1.
[0055] Figure 1 1 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, it can be seen that the negative electrode 100 for a lithium secondary battery includes a first negative electrode active material layer 20 and a second negative electrode active material layer 10 on one surface of a negative electrode collector layer 30 . Figure 1 The first negative electrode active material layer is shown to be formed on one surface of the negative electrode collector layer, but the first negative electrode active material layer may be formed on both surfaces of the negative electrode collector layer. As described above, in an exemplary embodiment of the present application, the first negative electrode active material layer may be formed on the entire surface of the negative electrode collector layer, and the second negative electrode active material layer may be formed on the entire surface of the first negative electrode active material layer.
[0056] also, Figure 2 is a diagram showing a stacked structure of a negative electrode for a lithium secondary battery according to an exemplary embodiment of the present application. Specifically, Figure 2 As shown in , the first negative electrode active material layer 20 and the second negative electrode active material layer 10 may be formed on both surfaces of the negative electrode collector layer 30. In addition, it may be an arrangement of 10>20>30>20>10. In addition, when the first negative electrode active material layer and the second negative electrode active material layer are sequentially stacked only on one surface of the negative electrode collector layer, the negative electrode active material layers may be stacked on the opposite surface in any arrangement, such as 10>20>30>20, 10>20>30>10, 10>20>30>10>20, etc. Preferably, the two surfaces of the negative electrode collector layer have the same composition, specifically, it may have a structure of 10>20>30>20>10.
[0057] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.
[0058] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the negative electrode for the lithium secondary battery comprises a negative electrode collector layer and a negative electrode active material layer arranged on one surface or both surfaces of the negative electrode collector layer, wherein the negative electrode active material layer comprises a first negative electrode active material layer arranged on the negative electrode collector layer and a second negative electrode active material layer arranged on a surface of the first negative electrode active material layer opposite to a surface facing the negative electrode collector layer.
[0059] In an exemplary embodiment of the present application, the thickness of the negative electrode current collector layer is generally 1 μm to 100 μm. There is no particular limitation on such a negative electrode current collector layer as long as it has high electrical conductivity and does not cause chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, etc., aluminum-cadmium alloy, etc. may be used. In addition, the negative electrode current collector layer may have fine irregularities formed on the surface to enhance the bonding force of the negative electrode active material, and may be used in various forms such as a film, sheet, foil, net, porous body, foam body or non-woven fabric body.
[0060] In an exemplary embodiment of the present application, the thickness of the negative electrode current collector layer may be 1 μm or more and 100 μm or less.
[0061] However, the thickness can be variously changed according to the type and use of the negative electrode used, and is not limited thereto.
[0062] In an exemplary embodiment of the present application, the first negative electrode active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and relative to 100 parts by weight of the first negative electrode active material, the content of SiOx (x = 0) may be 95 parts by weight or more.
[0063] In an exemplary embodiment of the present application, the first negative electrode active material may include one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and relative to 100 parts by weight of the first negative electrode active material, the content of SiOx (x = 0) may be 95 parts by weight or more, preferably 97 parts by weight or more, more preferably 99 parts by weight or more, and may be 100 parts by weight or less.
[0064] In an exemplary embodiment of the present application, in particular, pure silicon (Si) particles may be used as the first negative electrode active material. Using pure silicon (Si) as the first negative electrode active material may mean, as described above, pure Si particles (SiOx (x = 0)) that are not combined with other particles or elements within the above range relative to a total of 100 parts by weight of the first negative electrode active material.
[0065] In an exemplary embodiment of the present application, the first negative electrode active material may be composed of SiOx (x = 0).
[0066] The first negative electrode active material layer according to the present application comprises the first negative electrode active material, specifically, comprises pure silicon particles containing 95 parts by weight or more of SiOx (x=0). When a high content of pure silicon particles is included, the capacity characteristics are excellent, but the life characteristics are deteriorated due to uneven reactions on the surface. Therefore, a second negative electrode active material layer according to the present invention comprising a specific weight loading amount is provided to solve the above-mentioned problem.
[0067] Note that the average particle size (D50) of the first negative electrode active material of the present invention can be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within a suitable range, so that the viscosity of the formed negative electrode slurry is within an appropriate range. Therefore, the particles constituting the negative electrode slurry are smoothly dispersed. In addition, when the value of the size of the first negative electrode active material is equal to or greater than the lower limit of the range, due to the composite composed of a conductive material and a binder in the negative electrode slurry, the contact area between the silicon particles and the conductive material is excellent, thereby increasing the possibility of a continuous conductive network, thereby increasing the capacity retention rate. Note that when the average particle size satisfies the above range, excessively large silicon particles are excluded, thereby smoothly forming the negative electrode surface. As a result, the current density non-uniformity during charge and discharge can be prevented.
[0068] In an exemplary embodiment of the present application, the first negative electrode active material generally has a characteristic BET specific surface area. The BET specific surface area of the first negative electrode active material is preferably 0.01 m 2 / g to 150.0 m 2 / g, more preferably 0.1 m 2 / g to 100.0 m 2 / g, particularly preferably 0.2 m 2 / g to 80.0 m 2 / g, and most preferably 0.2 m 2 / g to 18.0m 2 The BET specific surface area is measured according to DIN 66131 (using nitrogen).
[0069] In an exemplary embodiment of the present application, the first negative electrode active material may be present, for example, in a crystalline form or an amorphous form, preferably non-porous. The silicon particles are preferably spherical or fragmentary particles. Alternatively but less preferably, the silicon particles may also have a fibrous structure or may be present in the form of a silicon-containing film or coating.
[0070] In an exemplary embodiment of the present application, the first negative electrode active material may have a non-spherical shape, and the sphericity (circularity) thereof is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0071] In the present application, the sphericity is determined by formula A-1, where A is the area and P is the boundary line.
[0072] [Formula A-1]
[0073] 4πA / P 2
[0074] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein a content of the first negative electrode active material is 60 parts by weight or more relative to 100 parts by weight of the first negative electrode active material layer composition.
[0075] In another exemplary embodiment, the content of the first negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and may be 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, relative to 100 parts by weight of the first negative electrode active material layer composition.
[0076] Although the first negative electrode active material layer composition according to the present application uses the first negative electrode active material having a significantly high capacity within the above range, the negative electrode also uses the second negative electrode active material layer as described below, thereby solving the problems of surface degradation during charge and discharge, uniformity during pre-lithiation, and life characteristics without reducing the overall capacity performance of the negative electrode.
[0077] In the related art, only graphite compounds are usually used as negative electrode active materials. However, in recent years, with the increasing demand for high-capacity batteries, attempts to mix silicon-based compounds to increase capacity have increased. However, the silicon-based compounds have the following limitations: the volume expands rapidly during the charge and discharge process, resulting in damage to the conductive path formed in the negative electrode active material layer, thereby deteriorating the performance of the battery.
[0078] Therefore, in an exemplary embodiment of the present application, the first negative electrode active material layer composition may further include one or more selected from the group consisting of a first negative electrode conductive material and a first negative electrode binder.
[0079] In this case, as the first negative electrode conductive material and the first negative electrode binder included in the first negative electrode active material layer composition, those used in the art may be used without limitation.
[0080] In an exemplary embodiment of the present application, as the first negative electrode conductive material, materials commonly used in the art may be used without limitation, and specifically, may include one or more selected from the group consisting of point conductive materials, planar conductive materials, and linear conductive materials.
[0081] In an exemplary embodiment of the present application, the dot-shaped conductive material refers to a conductive material that can be used to improve the conductivity of the negative electrode, has conductivity without causing chemical changes, and has a dot-shaped or spherical shape. Specifically, the dot-shaped conductive material can be selected from one or more of the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and preferably contains carbon black in terms of high conductivity and excellent dispersibility.
[0082] In an exemplary embodiment of the present application, the BET specific surface area of the dot-shaped conductive material may be 40 m 2 / g and above 70 m 2 / g or less, preferably 45 m 2 / g and above 65 m 2 / g or less, more preferably 50 m 2 / g or more and 60m 2 / g or less.
[0083] In an exemplary embodiment of the present application, the particle size of the dot-shaped conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0084] In an exemplary embodiment of the present application, the first negative electrode conductive material may include a planar conductive material.
[0085] The planar conductive material can be used to improve conductivity by increasing surface contact between silicon particles in the negative electrode while suppressing disconnection of the conductive path due to volume expansion, and can be expressed as a plate-like conductive material or a bulk-type conductive material.
[0086] In an exemplary embodiment of the present application, the planar conductive material may include one or more selected from the group consisting of plate-like graphite, graphene, graphene oxide, and graphite flakes, and may preferably be plate-like graphite.
[0087] In an exemplary embodiment of the present application, the average particle size (D50) of the planar conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. When the above range is met, sufficient particle size allows easy dispersion without causing excessive increase in viscosity of the negative electrode slurry. Therefore, when the same equipment and time are used for dispersion, the dispersion effect is excellent.
[0088] In an exemplary embodiment of the present application, a negative electrode composition is provided, wherein the planar conductive material has a D10 of 0.5 μm to 1.5 μm, a D50 of 2.5 μm to 3.5 μm, and a D90 of 7.0 μm to 15.0 μm.
[0089] In an exemplary embodiment of the present application, for the planar conductive material, a high specific surface area planar conductive material having a high BET specific surface area, or a low specific surface area planar conductive material may be used.
[0090] In an exemplary embodiment of the present application, for the planar conductive material, a planar conductive material with a high specific surface area or a planar conductive material with a low specific surface area can be used without restriction. However, in particular, the planar conductive material according to the present application may be affected by the dispersion effect to a certain extent in terms of electrode performance, so it is particularly preferred to use a planar conductive material with a low specific surface area that does not cause problems in terms of dispersion.
[0091] In an exemplary embodiment of the present application, the BET specific surface area of the planar conductive material may be 5 m 2 / g or above.
[0092] In another exemplary embodiment, the BET specific surface area of the planar conductive material may be 5 m 2 / g and above 500 m 2 / g or less, preferably 5 m 2 / g and above 300 m 2 / g or less, more preferably 5 m 2 / g and above 250 m 2 / g or less.
[0093] In another exemplary embodiment, the planar conductive material is a planar conductive material with a high specific surface area, and the BET specific surface area may satisfy 50 m 2 / g and above 500 m 2 / g or less, preferably 80 m 2 / g and above 300 m 2 / g or less, more preferably 100 m 2 / g and above 300 m2 / g or less.
[0094] In another exemplary embodiment, the planar conductive material is a planar conductive material with a low specific surface area, and the BET specific surface area may satisfy 5 m 2 / g and above 40 m 2 / g or less, preferably 5 m 2 / g and above 30 m 2 / g or less, more preferably 5 m 2 / g and above 25 m 2 / g or less.
[0095] Other conductive materials may include linear conductive materials, such as carbon nanotubes. The carbon nanotubes may be bundle-type carbon nanotubes. The bundle-type carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle-type" herein refers to a secondary shape in which a plurality of carbon nanotube units are arranged side by side or are wound in a bundle or rope-like manner in a manner that the longitudinal axis orientation of the carbon nanotube units is substantially the same. The carbon nanotube unit has a cylindrical graphite sheet with a nanometer-sized diameter and has an sp2 bonding structure. In this case, the characteristics of a conductor or a semiconductor may be exhibited according to the curling angle and structure of the graphite sheet. Compared with the wound carbon nanotubes, the bundle-type carbon nanotubes can be more evenly dispersed during the manufacture of the negative electrode, and can more smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0096] In an exemplary embodiment of the present application, the first negative electrode conductive material may satisfy a range of 10 parts by weight or more and 40 parts by weight or less relative to 100 parts by weight of the first negative electrode active material layer composition.
[0097] In another exemplary embodiment, the content of the first negative electrode conductive material may be 1 part by weight or more and 40 parts by weight or less, preferably 3 parts by weight or more and 30 parts by weight or less, and more preferably 5 parts by weight or more and 25 parts by weight or less, relative to 100 parts by weight of the first negative electrode active material layer composition.
[0098] In an exemplary embodiment of the present application, the first negative electrode conductive material may include a point conductive material, a planar conductive material, and a linear conductive material, and a ratio of the point conductive material: the planar conductive material: the linear conductive material may satisfy 1:1:0.01 to 1:1:1.
[0099] In an exemplary embodiment of the present application, the dot-shaped conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, relative to 100 parts by weight of the first negative electrode conductive material.
[0100] In an exemplary embodiment of the present application, the planar conductive material may satisfy a range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, relative to 100 parts by weight of the first negative electrode conductive material.
[0101] In an exemplary embodiment of the present application, the linear conductive material may satisfy a range of 0.01 parts by weight to 10 parts by weight, preferably 0.05 parts by weight to 8 parts by weight, and more preferably 0.1 parts by weight to 5 parts by weight, relative to 100 parts by weight of the first negative electrode conductive material.
[0102] In an exemplary embodiment of the present application, the first negative electrode conductive material may include a linear conductive material and a planar conductive material.
[0103] In an exemplary embodiment of the present application, the first negative electrode conductive material may include a linear conductive material and a planar conductive material, and a weight ratio of the linear conductive material to the planar conductive material may satisfy 0.01:1 to 0.1:1.
[0104] In an exemplary embodiment of the present application, since the first negative electrode conductive material satisfies the above-mentioned composition and ratio, the first negative electrode conductive material has the following characteristics: the life characteristics of the existing lithium secondary battery are not greatly affected, and the number of sites at which the battery can be charged and discharged is increased, so the output characteristics at a high C rate are excellent.
[0105] The first negative electrode conductive material according to the present application has a completely different structure from the conductive material applied to the positive electrode. That is, the first negative electrode conductive material according to the present application is used to maintain contact between the silicon-based active material in which the electrode volume expansion caused by charging and discharging is very large, while the positive electrode conductive material is used to play a buffering role during rolling while imparting a certain conductivity, and is completely different from the negative electrode conductive material of the present invention in terms of structure and function.
[0106] In addition, the first negative electrode conductive material according to the present application is applied to the silicon-based active material and has a completely different structure from the conductive material applied to the graphite-based active material. That is, since the conductive material used for the electrode with the graphite-based active material simply has smaller particles than the active material, the conductive material has the characteristics of improving output characteristics and imparting a certain conductivity, and is completely different from the first negative electrode conductive material applied together with the silicon-based active material in the present invention in terms of structure and function.
[0107] In an exemplary embodiment of the present application, the first negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, polyacrylic acid, and the above materials in which hydrogen is replaced by Li, Na, Ca, etc., and may also include various copolymers thereof.
[0108] The first negative electrode binder according to an exemplary embodiment of the present application is used to retain the first negative electrode active material and the first negative electrode conductive material so as to prevent the negative electrode structure from being distorted and deformed when the first negative electrode active material expands and relaxes. When such a role is met, all conventional binders can be applied. Specifically, an aqueous binder can be used, and more specifically, a PAM-based binder can be used.
[0109] In an exemplary embodiment of the present application, the content of the first negative electrode binder may be 30 parts by weight or less, preferably 25 parts by weight or less, more preferably 20 parts by weight or less, and may be 5 parts by weight or more and 10 parts by weight or more, relative to 100 parts by weight of the first negative electrode active material layer composition.
[0110] Compared with the existing carbon-based negative electrode, when using a Si-based negative electrode, the aqueous binder is applied according to the above weight parts, so that the dot-shaped conductive material can be used. In addition, the above characteristics make the dot-shaped conductive material hydrophobic and make the conductive material and the binder have excellent bonding strength.
[0111] In an exemplary embodiment of the present application, the second negative electrode active material may include one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0112] In another exemplary embodiment, the second negative electrode active material may include one or more and three or less selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0113] In another exemplary embodiment, the second negative electrode active material may include a carbon-based active material and a silicon-based active material.
[0114] In another exemplary embodiment, the second negative electrode active material may include a silicon-based active material.
[0115] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, and the content of the silicon-based active material is 50 parts by weight or more and 100 parts by weight or less with respect to 100 parts by weight of the second negative electrode active material.
[0116] In another exemplary embodiment, the second negative electrode active material may include one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0117] In an exemplary embodiment of the present application, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy.
[0118] In an exemplary embodiment of the present application, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy, and the content of SiOx (0 < x < 2) may be 1 part by weight or more with respect to 100 parts by weight of the second negative electrode active material.
[0119] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy, and the content of SiOx (0 < x < 2) may be 1 part by weight or more or 10 parts by weight or more and may be 99 parts by weight or less with respect to 100 parts by weight of the second negative electrode active material.
[0120] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include SiOx (0 < x < 2).
[0121] In another exemplary embodiment, the silicon-based active material included in the second negative electrode active material may include SiC.
[0122] As described above, the negative electrode for lithium secondary battery according to the present application includes the second negative electrode active material in the second negative electrode active material layer. Therefore, while maintaining high capacity characteristics and high density characteristics by including the above-mentioned first negative electrode active material, the second negative electrode active material is used as a buffer layer, thereby solving the surface degradation problem during charge and discharge, the uniformity problem during pre-lithiation, and the life characteristic problem.
[0123] As an example, the second negative electrode active material layer of the present application can be used as a buffer layer. Compared with electrodes containing SiO or carbon-based active materials, electrodes containing Si active materials have excellent capacity characteristics. However, in electrodes containing Si active materials, due to the rapid reaction with Li ions during charge and discharge, degradation is concentrated on the surface of the negative electrode active material layer. This also occurs in a pre-lithiation process in which lithium ions are pre-incorporated into the negative electrode active material layer. In the pre-lithiation process, a buffer layer is used to prevent direct contact between the Si-based electrode and lithium and to prevent surface degradation. Therefore, the second negative electrode active material layer of the present invention has the characteristic of being able to exhibit the same action and effect as a buffer layer during the pre-lithiation process.
[0124] In an exemplary embodiment of the present application, representative examples of the carbon-based active material include natural graphite, artificial graphite, expandable graphite, carbon fiber, difficult-graphitizable carbon, carbon black, carbon nanotubes, fullerenes, activated carbon, etc., and the carbon-based active material can be used without restriction as long as the carbon-based active material is generally used for carbon materials for lithium secondary batteries, specifically, it can be processed into a spherical or dot shape for use.
[0125] In an exemplary embodiment of the present application, the planar conductive material used as the first negative electrode conductive material has a structure and function different from the carbon-based active material generally used as the negative electrode active material. Specifically, the carbon-based active material used as the negative electrode active material may be artificial graphite or natural graphite, and refers to a material processed into a spherical or dot-like shape for use to promote lithium ion storage and release.
[0126] On the other hand, the planar conductive material used as the first negative electrode conductive material is a material having a planar or plate-like shape, and may be in the form of plate-like graphite. That is, the planar conductive material is a material contained in order to maintain a conductive path in the negative electrode active material layer, and refers to a material that ensures a conductive path in a planar shape inside the negative electrode active material layer rather than a material that plays a role in storing and releasing lithium.
[0127] That is, in the present application, using plate-like graphite as a conductive material means processing graphite into a planar or plate-like shape and using it as a material that ensures a conductive path rather than a material that plays a role in storing or releasing lithium. In this case, the negative electrode active material contained together has high capacity characteristics in terms of storing and releasing lithium, and plays a role in storing and releasing all lithium ions transferred from the positive electrode.
[0128] On the other hand, in the present application, using a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and used as a material for storing or releasing lithium.
[0129] That is, in an exemplary embodiment of the present application, the BET specific surface area of artificial graphite or natural graphite as a carbon-based active material may satisfy 0.1 m 2 / g or more and 4.5 m 2 In addition, the plate-like graphite as a planar conductive material has a planar shape and a BET specific surface area of 5 m 2 / g or above.
[0130] Representative examples of the metal-based active material may be compounds containing any one or two or more metal elements selected from the group consisting of Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, Sb, Ga, Mn, Fe, Co, Ni, Cu, Sr, and Ba. These metal compounds may be used in any form, such as a simple substance, an alloy, an oxide (TiO 2 SnO 2 etc.), nitrides, sulfides, borides and alloys with lithium, but the single substance, alloys, oxides and alloys with lithium may be improved in capacity.
[0131] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the content of the second negative electrode active material is 60 parts by weight or more relative to 100 parts by weight of the second negative electrode active material layer composition.
[0132] In another exemplary embodiment, the second negative electrode active material may satisfy a range of 60 parts by weight or more and 100 parts by weight or less or 99 parts by weight or less, relative to 100 parts by weight of the second negative electrode active material layer composition.
[0133] The second negative electrode active material layer composition according to the present application has the characteristic of suppressing the surface reaction of the negative electrode to enhance the life characteristics without deteriorating the capacity performance of the negative electrode by using a second negative electrode active material within the above range (compared with the first negative electrode active material, the capacity characteristics are lower but the particle cracking during charge and discharge is less).
[0134] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material layer composition further includes one or more selected from the group consisting of a second negative electrode conductive material and a second negative electrode binder.
[0135] In this case, descriptions about the second negative electrode conductive material and the second negative electrode binder may be the same as the above descriptions about the first negative electrode conductive material and the first negative electrode binder.
[0136] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the ratio of amorphous silicon contained in the first negative electrode active material layer is lower than the ratio of amorphous silicon contained in the second negative electrode active material layer, wherein the ratio of the silicon phase contained in the negative electrode active material layer satisfies the following formula 1:
[0137] [Formula 1]
[0138] 5 ≤ B / (A+B)×100(%) ≤ 30
[0139] In the above formula 1,
[0140] A refers to the weight parts of the crystalline phase relative to 100 weight parts of the silicon phase contained in the negative electrode active material layer, and
[0141] B refers to the weight parts of the amorphous phase relative to 100 weight parts of the silicon phase included in the negative electrode active material layer.
[0142] In an exemplary embodiment of the present application, the above Formula 1 may satisfy 5≤B / (A+B)×100(%)≤30, preferably 6≤B / (A+B)×100(%)≤25, and more preferably 7≤B / (A+B)×100(%)≤25.
[0143] Compared with the case of using a single-layer silicon-based active material layer in the related art, the negative electrode for lithium secondary batteries according to the present application can achieve high C rate charging during the activation process, thereby shortening the activation process itself, and at the same time can adjust the ratio of the silicon phase in the negative electrode active material layer to the range of the above formula 1. Therefore, the manufacturing process time of the negative electrode for lithium secondary batteries can be shortened, and high capacity characteristics and room temperature life characteristics can be ensured.
[0144] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the second negative electrode active material layer contains amorphous silicon and crystalline silicon, and the content of the amorphous phase is 90 parts by weight or more relative to 100 parts by weight of the silicon phase contained in the second negative electrode active material layer.
[0145] In another exemplary embodiment, the second negative electrode active material layer may contain amorphous silicon and crystalline silicon, and the amorphous phase may satisfy a range of 90 parts by weight or more, preferably 91 parts by weight or more, and specifically 99 parts by weight or less or 95 parts by weight or less, relative to 100 parts by weight of the silicon phase contained in the second negative electrode active material layer.
[0146] In other words, the second negative electrode active material layer (upper layer) acts as a buffer layer and is coated to a minimum thickness to achieve high rate activation, and the high capacity and high density first negative electrode active material layer has a significant influence on negative electrode performance.
[0147] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the first negative electrode active material layer contains amorphous silicon and crystalline silicon, and the content of the crystalline phase is 50 parts by weight or more relative to 100 parts by weight of the silicon phase contained in the first negative electrode active material layer.
[0148] In another exemplary embodiment, the first negative electrode active material layer may contain amorphous silicon and crystalline silicon, and the crystalline phase may satisfy a range of 60 parts by weight or more, preferably 65 parts by weight or more, and specifically 99 parts by weight or less or 95 parts by weight or less, relative to 100 parts by weight of the silicon phase contained in the first negative electrode active material layer.
[0149] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein when the total thickness of the negative electrode active material layer is defined as T, the negative electrode active material layer includes a first region within a range of less than 0.2T and a second region within a range of greater than 0.5T and less than 1T based on the surface opposite to the surface facing the negative electrode collector layer, wherein the content of the amorphous phase in the first region is 90 parts by weight or more relative to 100 parts by weight of the silicon phase in the negative electrode active material layer, and wherein the content of the crystalline phase in the second region is 60 parts by weight or more relative to 100 parts by weight of the silicon phase in the negative electrode active material layer.
[0150] In an exemplary embodiment of the present application, the total thickness T of the negative electrode active material layer may refer to the total thickness of the thickness of the first negative electrode active material layer and the thickness of the second negative electrode active material layer, and the regions as described above may be divided and represented based on the total thickness. In this case, the surface serving as the thickness measurement reference may be the surface of the second negative electrode active material layer opposite to the surface facing the first negative electrode active material layer.
[0151] In other words, the negative electrode active material layer according to the present application is formed as a double layer in which the first negative electrode active material layer and the second negative electrode active material layer are stacked, and high-rate charging during the activation process is achieved by having the second negative electrode active material layer. Therefore, the ratio of the silicon phase in the negative electrode for the lithium secondary battery satisfies the above-mentioned range.
[0152] In the present application, the arrangement of the silicon phase can be confirmed by Raman analysis of the negative electrode for the lithium secondary battery through the change of the silicon phase in the depth direction, and the weight distribution ratio of the silicon phase in the negative electrode can be confirmed by the analysis. In this case, the activation process is performed on the surface portion of the negative electrode active material layer. Considering that the surface portion of the negative electrode active material layer (the region away from the negative electrode collector layer) contains an amorphous phase, and the interior of the negative electrode active material layer (the region close to the negative electrode collector layer) contains a crystalline phase, based on the weight ratio of the silicon phase, each region is divided and represented according to thickness (T).
[0153] The region can be roughly divided into an amorphous phase region, a crystalline phase region, and a mixed region of the amorphous phase and the crystalline phase. The first region can be represented as an amorphous phase region, the second region can be represented as a crystalline phase region, and the middle region of the above range (i.e., a region greater than 0.2T and less than 0.5T) can be represented as a mixed region of the amorphous phase and the crystalline phase.
[0154] By adjusting the distribution of the crystalline phase and the amorphous phase as described above, high capacity and high energy density characteristics can be achieved while achieving excellent room temperature cycle life.
[0155] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the viscosity of the first negative electrode active material layer composition is a shear viscosity of more than 2,000 cPs and less than 15,000 cPs at a shear rate of 2.5 (1 / s), and the viscosity of the second negative electrode active material layer composition is lower than the viscosity of the first negative electrode active material layer composition.
[0156] In another exemplary embodiment, the viscosity of the first negative active material layer composition may satisfy a shear viscosity of 2,000 cPs to 15,000 cPs, preferably 2,300 cPs to 14,000 cPs, and more preferably 2,500 cPs to 12,000 cPs at a shear rate of 2.5 (1 / s).
[0157] In this case, the viscosity of the second negative electrode active material layer composition should be maintained lower than that of the first negative electrode active material layer composition, so that a double-layer negative electrode active material layer as described in the present application can be formed. More specifically, the viscosity of the second negative electrode active material layer composition should be lower than but similar to that of the first negative electrode active material layer composition.
[0158] In an exemplary embodiment of the present application, the negative electrode for a lithium secondary battery can be prelithiated.
[0159] The negative electrode for a lithium secondary battery according to the present application is composed of a double layer. In particular, high-rate charging can be achieved during the activation process, which helps to adjust the ratio of the silicon phase in the negative electrode active material layer, thereby ensuring uniform lithiation in the depth direction of the electrode during future charge-discharge cycles.
[0160] An exemplary embodiment of the present application provides a lithium secondary battery, which includes a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0161] The secondary battery according to an exemplary embodiment of the present specification may particularly include the above-mentioned negative electrode for a lithium secondary battery. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the above-mentioned negative electrode. Since the negative electrode has been described above, its detailed description is omitted.
[0162] An exemplary embodiment of the present application provides a method for manufacturing a lithium secondary battery, the method including: preparing a lithium secondary battery, the lithium secondary battery including a positive electrode, a negative electrode for a lithium secondary battery, a separator, and an electrolyte; and activating the lithium secondary battery, wherein the activation includes a high C-rate activation process (high-rate charging, specifically above 1C rate), and wherein preparing the negative electrode for a lithium secondary battery includes: preparing a negative electrode current collector layer, forming a first negative electrode active material layer by applying a first negative electrode active material layer composition to one or two surfaces of the negative electrode current collector layer using a coater, and forming a second negative electrode active material layer by applying a second negative electrode active material layer composition to the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer, wherein the first negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more relative to 100 parts by weight of the first negative electrode active material, and wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
[0163] In the manufacturing method, the above description can be applied to the composition and content included in each step.
[0164] That is, as described above, the second negative electrode active material layer is also formed instead of the first negative electrode active material layer alone, which enables high rate charging during the activation process to arrange the silicon phase of Formula 1 above, thereby ensuring life characteristics.
[0165] In an exemplary embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the thickness of the second negative electrode active material layer is 25% to 45% of the total thickness of the first negative electrode active material layer and the second negative electrode active material layer.
[0166] In another exemplary embodiment, the thickness of the first negative electrode active material layer may be 10 μm or more and 200 μm or less, specifically 15 μm or more and 190 μm or less, and more specifically 20 μm or more and 170 μm or less.
[0167] In another exemplary embodiment, the thickness of the second negative electrode active material layer may be 5 μm or more and 150 μm or less, specifically 6 μm or more and 145 μm or less, and more specifically 7 μm or more and 140 μm or less.
[0168] An exemplary embodiment of the present application includes forming a first negative electrode active material layer by applying a first negative electrode active material layer composition on one surface or both surfaces of the negative electrode collector layer using a coater.
[0169] That is, this step is a step of forming an active material layer on the negative electrode current collector layer, and may refer to a step of forming an active material layer on a surface (lower layer portion) in contact with the negative electrode current collector layer in a double-layer structure.
[0170] In an exemplary embodiment of the present application, applying the first negative electrode active material layer composition includes applying a first negative electrode slurry including the first negative electrode active material layer composition and a negative electrode slurry solvent and drying it.
[0171] In this case, the solid content of the first negative electrode slurry may satisfy a range of 10% to 40%.
[0172] In an exemplary embodiment of the present application, forming the first negative electrode active material layer may include: mixing the first negative electrode slurry; and coating the mixed first negative electrode slurry on one surface or both surfaces of the negative electrode collector layer by a coater, and the coating may be performed using a coating method commonly used in the art.
[0173] An exemplary embodiment of the present application includes forming a second negative active material layer by applying a second negative active material layer composition to a surface of the first negative active material layer opposite to a surface contacting the negative current collector layer using a coater.
[0174] That is, this step is a step of forming a second negative electrode active material layer on the first negative electrode active material layer, and may refer to a step of forming an active material layer on a surface (upper layer portion) away from the negative electrode collector layer in a double-layer structure.
[0175] In an exemplary embodiment of the present application, applying the second negative electrode active material layer composition includes applying a second negative electrode slurry including the second negative electrode active material layer composition and a negative electrode slurry solvent and drying it.
[0176] In this case, the solid content of the second negative electrode slurry may satisfy a range of 10% to 40%.
[0177] In an exemplary embodiment of the present application, a method for manufacturing a lithium secondary battery is provided, wherein forming the second negative electrode active material layer may include: mixing the second negative electrode slurry, and coating the mixed second negative electrode slurry on a surface of the first negative electrode active material layer opposite to a surface contacting the negative electrode collector layer.
[0178] The coating may be performed using a coating method generally used in the art.
[0179] The description of forming the first negative electrode active material layer may be applied to forming the second negative electrode active material layer.
[0180] In an exemplary embodiment of the present application, a method of manufacturing a lithium secondary battery is provided, wherein forming the second negative electrode active material layer on the first negative electrode active material layer may include a wet-on-dry process or a wet-on-wet process.
[0181] In an exemplary embodiment of the present application, the wet-on-dry process may refer to a process of applying a first negative electrode active material layer composition, partially or completely drying the composition, and applying a second negative electrode active material layer composition on an upper portion of the composition.
[0182] Figure 3is a flow chart showing a wet-cover-dry process according to an exemplary embodiment of the present application. Specifically, in the wet-cover-dry process, a first negative electrode slurry mixture (a first negative electrode active material, a first negative electrode conductive material, a first negative electrode binder, a first solvent) is prepared and applied to the negative electrode collector layer. Then, the first negative electrode slurry mixture is dried to form a first negative electrode active material layer. Then, a second negative electrode slurry mixture is prepared, applied to the first negative electrode active material layer and dried to form a second negative electrode active material layer. Then, the individual layers can be rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.
[0183] In an exemplary embodiment of the present application, the wet-on-wet process refers to a process of applying the first negative electrode active material layer composition and applying the second negative electrode active material layer composition on the upper portion of the first negative electrode active material layer composition without drying it.
[0184] Figure 4 is a flow chart showing a wet-on-wet process according to an exemplary embodiment of the present application. Specifically, in the wet-on-wet process, a first negative electrode slurry mixture is prepared and applied to a negative electrode current collector layer, and a second negative electrode slurry mixture is prepared and applied to the first negative electrode slurry mixture, and then the first negative electrode slurry mixture and the second negative electrode slurry mixture are dried. Then, the layers can be rolled and pressed to form a negative electrode for a lithium secondary battery according to the present application.
[0185] In particular, the wet-on-dry process applies the first negative electrode active material layer composition, completely dries the composition, and then applies the second negative electrode active material layer composition thereon, and through the above process, the first negative electrode active material layer and the second negative electrode active material layer can have a clear boundary. Thus, the compositions contained in the first negative electrode active material layer and the second negative electrode active material layer are not mixed, so that a double layer can be constructed.
[0186] In an exemplary embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve the first negative electrode active material layer composition and the second negative electrode active material layer composition, and specifically, water or NMP may be used.
[0187] As a result of the wet-on-wet process described above, a junction region in which the first negative electrode active material layer is mixed with the second negative electrode active material layer may be formed. In this case, in order to perform the wet-on-wet process, the viscosity of the first negative electrode active material layer composition should be lower than the viscosity of the second negative electrode active material layer composition so that mutual mixing occurs in the junction region and the process. The viscosity range should be met to ensure stable double-layer coating during the wet-on-wet process.
[0188] In the present application, after the first negative electrode active material layer is dried (wet-cover-dry process), the second negative electrode active material layer is formed, thereby clearly dividing the interface between the two layers. In addition, when the second negative electrode active material layer composition is applied when the first negative electrode active material layer composition is not completely dried (the first negative electrode active material layer composition and the second negative electrode active material layer composition are applied at the same time), mixing occurs at the interface of the two layers, thereby forming a bonding area. In this case, it is not desirable to generate a mixed area in the wet-cover-dry process. In order to ensure the wet-cover-dry processability, as described above, the viscosity of the second negative electrode active material layer composition should be lower than the viscosity of the first negative electrode active material layer composition, so that the coating processability allows the coating to be well carried out to the edge of the coating.
[0189] In an exemplary embodiment of the present application, a method for manufacturing a lithium secondary battery is provided, the method comprising pre-lithiation of a negative electrode having the first negative electrode active material layer and the second negative electrode active material layer formed on the negative electrode collector layer, wherein the pre-lithiation of the negative electrode comprises a lithium plating process, a lithium metal transfer process, a lithium metal deposition process or a stabilized lithium metal powder (SLMP) coating process.
[0190] As described above, the second negative electrode active material layer contains the above-mentioned second negative electrode active material, and preferably may have a mixed composition of a silicon-based active material and a carbon-based active material, so that it can have the advantage of fast charging as it is. In particular, the second negative electrode active material may preferably have a mixed composition, and is therefore highly irreversible, which is advantageous even in the pre-lithiation process of pre-charging the negative electrode. Compared with the case where only the first negative electrode active material layer is simply applied, the second negative electrode active material layer contains the second negative electrode active material having the above-mentioned composition, so that a uniform pre-lithiation process can be performed on the upper part of the negative electrode, thereby improving the life span.
[0191] In an exemplary embodiment of the present application, the porosity of the first negative electrode active material layer and the second negative electrode active material layer may satisfy a range of 10% or more and 60% or less.
[0192] In another exemplary embodiment, the porosity of the first negative electrode active material layer and the second negative electrode active material layer may satisfy the range of 10% to 60%, preferably 20% to 50%, and more preferably 30% to 45%.
[0193] The porosity varies according to the composition and content of the active material, the conductive material, and the binder included in the first and second negative electrode active material layers, and thus, the conductivity and resistance of the electrode are within an appropriate range.
[0194] In an exemplary embodiment of the present application, the positive electrode may include a positive electrode collector layer and a positive electrode active material layer formed on the positive electrode collector layer and including a positive electrode active material.
[0195] In the positive electrode, there is no particular restriction on the positive electrode collector layer, as long as it has conductivity and does not cause chemical changes in the battery. For example, stainless steel, aluminum, nickel, titanium, fired carbon, aluminum or stainless steel treated with carbon, nickel, titanium, silver, etc., can be used. In addition, the thickness of the positive electrode collector can generally be 3 μm to 500 μm, and the surface of the collector can be formed with fine concave and convex to enhance the adhesion of the positive electrode active material. For example, the positive electrode collector layer can be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and non-woven fabrics.
[0196] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound, such as lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ) or compounds replaced with one or more transition metals; lithium iron oxides, such as LiFe 3 O 4 ; Lithium manganese oxide, such as the chemical formula Li 1+c1 Mn 2-c1 O 4 (0≤c1≤0.33), LiMnO 3 、LiMn 2 O 3 and LiMnO 2 ; Lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides, such as LiV 3 O 8 、V 2 O 5 and Cu 2 V 2 O 7 ; Ni-site lithium nickel oxide, with the chemical formula LiNi 1-c2 M c2 O 2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≤c2≤0.3); lithium manganese composite oxide, represented by the chemical formula LiMn2- c3 M c3 O 2 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn and Ta, and satisfies 0.01≤c3≤0.1) or Li 2 Mn 3 MO 8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu and Zn); LiMn 2 O 4 , wherein a portion of the Li in the chemical formula is replaced by an alkaline earth metal ion, etc., but not limited thereto. The positive electrode may be Li metal.
[0197] The positive electrode active material layer may further include a positive electrode conductive material and a positive electrode binder in addition to the positive electrode active material.
[0198] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without particular limitation, as long as the positive electrode conductive material has electronic conductivity without causing chemical changes in the constituted battery. Specific examples may include graphite such as natural graphite and artificial graphite; carbon materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, etc., and any one thereof or a mixture of two or more thereof may be used.
[0199] In addition, the positive electrode binder is used to improve the bonding between the positive electrode active material particles and the adhesion between the positive electrode active material and the positive electrode collector. Specific examples may include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or its various copolymers, and any one thereof or a mixture of two or more thereof may be used.
[0200] The diaphragm is used to separate the negative electrode from the positive electrode and provide a lithium ion movement path, wherein any diaphragm can be used as the diaphragm without particular limitation, as long as it is generally used for secondary batteries, in particular, it is preferred to use a diaphragm with high moisture retention capacity for electrolytes and low resistance to electrolyte ion movement. Specifically, a porous polymer film can be used, for example, a porous polymer film made of polyolefin-based polymers such as ethylene homopolymers, propylene homopolymers, ethylene / butene copolymers, ethylene / hexene copolymers and ethylene / methacrylate copolymers, or a laminated structure of more than two layers thereof. In addition, conventional porous non-woven fabrics can be used, such as non-woven fabrics formed of high melting point glass fibers, polyethylene terephthalate fibers, etc. In addition, a coated diaphragm comprising a ceramic component or a polymer material can be used to ensure heat resistance or mechanical strength, and a diaphragm with a single-layer or multilayer structure can be selectively used.
[0201] Examples of the electrolyte may include an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, or a molten-type inorganic electrolyte that may be used to manufacture a lithium secondary battery, but are not limited thereto.
[0202] Specifically, the electrolyte may include a nonaqueous organic solvent and a metal salt.
[0203] As the nonaqueous organic solvent, for example, an aprotic organic solvent such as N-methyl-2-pyrrolidone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, γ-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triester phosphate, trimethoxymethane, dioxolane derivatives, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ether, methyl propionate or ethyl propionate can be used.
[0204] Especially, in the carbonate-based organic solvent, ethylene carbonate and propylene carbonate as cyclic carbonate are high viscosity organic solvents and can be preferably used, because their dielectric constant is high, thereby lithium salt is well dissociated. When cyclic carbonate is low in viscosity and straight-chain carbonates with low dielectric constant such as dimethyl carbonate and diethyl carbonate are mixed with suitable ratio and used, high conductivity electrolyte can be prepared, so such combination can be more preferred.
[0205] As the metal salt, a lithium salt which is a material easily dissolved in the non-aqueous electrolyte may be used, wherein as anions of the lithium salt, for example, one or more species selected from the group consisting of: F -、Cl - 、I - 、NO 3 - 、N(CN) 2 - 、BF 4 - 、ClO 4 - 、PF 6 - 、(CF 3 ) 2 PF 4 - 、(CF 3 ) 3 PF 3 - 、(CF 3 ) 4 PF 2 - 、(CF 3 ) 5 PF - 、(CF 3 ) 6 P - 、CF 3 SO 3 - 、CF 3 CF 2 SO 3 - 、(CF 3 SO 2 ) 2 N - 、(FSO 2 ) 2 N - 、CF 3 CF 2 (CF 3 ) 2 CO - 、(CF 3 SO 2 ) 2 CH - 、(SF 5 ) 3 C - 、(CF 3 SO 2 ) 3 C - 、CF 3 (CF 2 ) 7 SO 3 - 、CF 3 CO2 - , CH 3 CO 2 - 、SCN - and (CF 3 CF 2 SO 2 ) 2 N - .
[0206] In order to improve the life characteristics of the battery, inhibit the decrease of the battery capacity, improve the discharge capacity of the battery, etc., in addition to the above-mentioned electrolyte components, the electrolyte may further contain one or more additives, such as halogenated alkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme dimethyl ether, hexamethylphosphoric triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol or aluminum trichloride.
[0207] An exemplary embodiment of the present invention provides a battery module and a battery pack including the same, wherein the battery module includes the secondary battery as a unit cell. Since the battery module and the battery pack include secondary batteries having high capacity, high rate capability, and high cycle characteristics, the battery module and the battery pack can be used as a power source for medium and large devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.
[0208] Mode for use in the present invention
[0209] Hereinafter, preferred embodiments will be provided for a better understanding of the present invention. It will be apparent to those skilled in the art that the embodiments are provided only to illustrate the present invention, and that various changes and variants are possible within the scope and technical concept of the present invention. Such changes and variants naturally fall within the scope of the claims contained herein.
[0210] <Preparation Example>
[0211] <Preparation of negative electrode>
[0212] Preparation of the first negative electrode active material layer
[0213] Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder were added to distilled water as a solvent for forming a negative electrode slurry at a weight ratio of 70:10:10:10 to prepare a first negative electrode slurry (solid concentration: 25 wt %).
[0214] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), the second conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm).
[0215] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare slurry.
[0216] The first negative electrode slurry was coated on both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector, and then rolled and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer.
[0217] Preparation of the second negative electrode active material layer
[0218] SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, artificial graphite as a carbon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder were added to distilled water as a negative electrode slurry forming solvent at a weight ratio of 50:30:5:5:10 to prepare a second negative electrode slurry (solid concentration: 25 wt %).
[0219] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), the second conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm).
[0220] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare slurry.
[0221] The second negative electrode slurry was coated on the first negative electrode active material layer, and then rolled and dried in a vacuum oven at 130° C. for 10 hours to form a second negative electrode active material layer.
[0222] <Preparation of Secondary Battery>
[0223] By using LiNi as the positive electrode active material 0.6 Co 0.2 Mn0.2 O 2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal Corporation) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry in a weight ratio of 97:1.5:1.5 to prepare a positive electrode slurry (solid concentration: 78 wt %).
[0224] The positive electrode slurry was prepared at 537 mg / 25 cm 2 The positive electrode was prepared by coating the positive electrode with a loading amount of 77 μm on both surfaces of an aluminum current collector (thickness: 12 μm) as a positive electrode current collector, and then rolling and drying in a vacuum oven at 130°C for 10 hours to form a positive electrode active material layer (thickness: 65 μm).
[0225] Lithium secondary batteries were manufactured by interposing a polyethylene separator between the positive electrode and the negative electrode of the examples and comparative examples and injecting an electrolyte.
[0226] The electrolyte is obtained by adding 3 wt % of vinylene carbonate to an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) are mixed in a volume ratio of 30:70, and adding LiPF 6 to a concentration of 1 M.
[0227] Then, an activation process was performed under the conditions shown in Table 1 below, and the results are shown in Table 2 below.
[0228]
[0229]
[0230] Figure 5 is a diagram showing the silicon phase distribution obtained by Raman analysis of the negative electrodes for lithium secondary batteries according to Examples 1 to 4 of the present application, Figure 6 : is a figure which shows the silicon phase distribution obtained by Raman analysis of the negative electrode for lithium secondary batteries of Comparative Examples 1 to 4 according to the present application.
[0231] Specifically, for the above-mentioned embodiments and comparative examples, the silicon phase change in the depth direction of the electrode was confirmed by Raman analysis of the first negative electrode active material layer of the cross-sectional electrode. Specifically, red (upper part) represents an amorphous phase, blue (bottom) represents a crystalline phase, and green (middle) can represent a mixture of an amorphous phase and a crystalline phase. In the case of the second negative electrode active material layer, the ratio of the amorphous phase is 95 parts by weight or more relative to the total silicon phase in the second negative electrode active material layer. However, the thickness of the second negative electrode active material layer is formed to be thinner than the thickness of the first negative electrode active material layer. Therefore, when considering the entire lithium secondary battery negative electrode, there is no significant difference except that the amorphous phase has a certain amount of increase in the Raman analysis of the first negative electrode active material layer (based on the total amount, an increase of 5 parts by weight to 7 parts by weight).
[0232] <Comparative Example 5>
[0233] Si (average particle size (D50): 5 μm) as a silicon-based active material, a first conductive material, a second conductive material, and polyacrylamide as a binder were added to distilled water as a solvent for forming a negative electrode slurry at a weight ratio of 70:10:10:10 to prepare a negative electrode slurry (solid concentration: 25 wt %).
[0234] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), the second conductive material is plate-like graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm).
[0235] As a mixing method, after the first conductive material, the second conductive material, the binder, and water were dispersed with a homomixer at 2500 rpm for 30 minutes, the active material was added to the dispersion and then dispersed at 2500 rpm for 30 minutes to prepare slurry.
[0236] The negative electrode slurry was coated on both surfaces of a copper current collector (thickness: 8 μm) as a negative electrode current collector, and then rolled and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer. Then, a positive electrode was prepared as in Example 1 above, and a lithium secondary battery was prepared in the same manner.
[0237] Then, an activation process was performed under the same conditions as in Example 1.
[0238] Figure 7: is a SEM photograph of a cross section of a negative electrode for a lithium secondary battery according to Comparative Example 5 of the present application. Specifically, by subjecting the battery to a charging process at a high rate of 1 C as in Example 1, it can be confirmed that the reaction is concentrated on the surface portion of the electrode made of pure Si and surface degradation occurs, and even before Raman analysis, the surface degradation reaction is easily observed only by the SEM photograph.
[0239] Experimental Example 1: Evaluation of Lifespan Characteristics
[0240] For the secondary battery comprising the negative electrode manufactured in the embodiment and the comparative example, the life and capacity retention rate were evaluated using an electrochemical charge and discharge device. The secondary battery was subjected to an in-situ cycle test at 4.2-3.0 V 1 C / 0.5 C, and during the test, 0.33 C / 0.33 C charge and discharge (4.2-3.0 V) was performed every 50 cycles to measure the capacity retention rate. In Table 3 below, the in-situ capacity retention rate is shown instead of the RPT capacity retention rate.
[0241] Capacity retention rate (%) = {(discharge capacity in the Nth cycle) / (discharge capacity in the first cycle)}×100
[0242] Experimental Example 2: Evaluation of resistance increase rate measurement
[0243] After measuring the capacity retention rate by charging and discharging the battery at 0.33 C / 0.33 C (4.2-3.0 V) every 50 cycles in the test of Experimental Example 1, the battery was discharged at SOC50 with a 2.5 C pulse, and then the resistance increase rate was compared and analyzed.
[0244] In addition, for the evaluation of the life characteristics and the evaluation of the resistance increase rate measurement, data at 200 cycles were each calculated, and the results are shown in Table 3 below.
[0245]
[0246] As can be seen in Table 3 above, it can be seen that when the lithium secondary battery according to the present application includes the second negative electrode active material layer and performs an activation process under the activation conditions in Table 1 above, a lithium secondary battery satisfying the optimal silicon phase can be manufactured.
[0247] Specifically, in the case of Examples 1 to 4 according to the present application, high-rate charging of 1 C or more was performed, and the second negative electrode active material layer was included, as shown in Table 2, it can be seen that the ratio of amorphous silicon to crystalline silicon satisfies the specific formula 1. In other words, it can be confirmed that even when the activation process is performed under high-rate (1 C or more) activation conditions, during the battery driving process, the capacity retention rate and the resistance increase rate meet a certain range, while minimizing the activation time, thereby being suitable for mass production processes.
[0248] That is, the negative electrode according to Examples 1 to 4 of the present application can ensure the processability of mass production by including a second negative electrode active material layer and a high-rate (above 1 C) activation process, and defines the ratio of amorphous silicon to crystalline silicon. Even if a high-rate (above 1 C) activation process is included, the capacity characteristics as in the related art are satisfied, and the resistance growth rate is also low.
[0249] Comparative Examples 1 to 4 correspond to the case where the same negative electrode as in the embodiment is measured while changing the activation conditions as shown in Table 1 above. In other words, it can be confirmed that in the activation process, when charging is performed for a long time under low charging conditions (low rate), the capacity characteristics and the resistance increase rate are excellent, but as in Comparative Examples 1 to 4, when the activation process time exceeds 2 hours, there is a problem in mass production and it is not suitable in terms of process.
[0250] In addition, the higher the SiO content contained in the second negative electrode active material layer, the better the retention rate. In addition, the SiO content in the second negative electrode active material layer composition can be adjusted to a degree that can improve the performance compared to the negative electrode containing Si as a single active material layer, and can be equal to or less than or greater than the content of Example 1.
[0251] For reference, Comparative Example 5 corresponds to the case of preparing a negative electrode having only the first negative electrode active material layer according to the present application, that is, a single active material layer structure. In this case, it can be seen that since the second negative electrode active material layer is not included, when the high-rate activation process described in Example 1 is performed, as shown in Example 1, the process properties can be ensured, but as shown in Table 3, the capacity retention rate is lower than that of Examples 1 to 4 of the present application, and the resistance increase rate is also higher than that of the embodiment. That is, it can be confirmed that during activation, the reaction is concentrated on the surface of the negative electrode containing only pure Si, resulting in rapid deterioration of the life characteristics due to surface degradation. That is, in this case, it is necessary to perform a low-rate activation process or other types of activation processes by adjusting the activation process conditions.
[0252] That is, as can be seen in Table 3, the batteries according to Examples 1 to 4 of the present application have characteristics that define the silicon phase state of the negative electrode for lithium secondary batteries, wherein the capacity retention rate and resistance characteristics exhibited can be equal to or higher than those of Comparative Examples 1 to 4 in which the process time is increased by applying a low-rate activation process, thereby ensuring processability.
Claims
1. A negative electrode for a lithium secondary battery, comprising: A negative electrode current collector layer; and A negative electrode active material layer formed on one or both surfaces of the negative electrode current collector layer, Wherein the negative electrode active material layer includes a first negative electrode active material layer provided on the negative electrode current collector layer and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to the surface facing the negative electrode current collector layer, Wherein the first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, and the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, Wherein the first negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more with respect to 100 parts by weight of the first negative electrode active material, Wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, Wherein the ratio of amorphous silicon contained in the first negative electrode active material layer is lower than the ratio of amorphous silicon contained in the second negative electrode active material layer, and Wherein the ratio of the silicon phase contained in the negative electrode active material layer satisfies the following formula 1: [Formula 1] 5 ≤ B / (A + B)×100(%) ≤ 30 In the above formula 1, A refers to the weight part of the crystalline phase with respect to 100 weight parts of the silicon phase contained in the negative electrode active material layer, and B refers to the weight part of the amorphous phase with respect to 100 weight parts of the silicon phase contained in the negative electrode active material layer.
2. The negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material layer includes amorphous silicon and crystalline silicon, and Wherein the content of the amorphous phase is 90 parts by weight or more with respect to 100 weight parts of the silicon phase contained in the second negative electrode active material layer.
3. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode active material layer includes amorphous silicon and crystalline silicon, and Wherein the content of the crystalline phase is 50 parts by weight or more with respect to 100 weight parts of the silicon phase contained in the first negative electrode active material layer.
4. The negative electrode for a lithium secondary battery according to claim 1, wherein when the total thickness of the negative electrode active material layer is defined as T, the negative electrode active material layer includes a first region within a range of 0.2T or less based on the surface opposite to the surface facing the negative electrode current collector layer and a second region within a range greater than 0.5T and T or less, Wherein the content of the amorphous phase is 90 parts by weight or more with respect to 100 weight parts of the silicon phase in the first region, and Wherein the content of the crystalline phase is 60 parts by weight or more with respect to 100 weight parts of the silicon phase in the second region.
5. The negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium nitride, and the content of the silicon-based active material is 65 parts by weight or more and 100 parts by weight or less based on 100 parts by weight of the second negative electrode active material.
6. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material includes one or more selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy.
7. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material includes SiOx (0 < x < 2).
8. The negative electrode for a lithium secondary battery according to claim 1, wherein the content of the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the first negative electrode active material layer composition.
9. The negative electrode for a lithium secondary battery according to claim 1, wherein the viscosity of the first negative electrode active material layer composition is a shear viscosity of 2,000 cPs or more and 15,000 cPs or less at a shear rate of 2.5 (1 / s), and wherein the viscosity of the second negative electrode active material layer composition is lower than the viscosity of the first negative electrode active material layer composition.
10. The negative electrode for a lithium secondary battery according to claim 1, wherein the first negative electrode active material layer is formed on the entire surface of the negative electrode current collector layer, and wherein the second negative electrode active material layer is formed on the entire surface of the first negative electrode active material layer.
11. A lithium secondary battery, comprising: a positive electrode; the negative electrode for a lithium secondary battery according to any one of claims 1 to 10; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
12. A method for manufacturing a lithium secondary battery, the method comprising: preparing a lithium secondary battery, the lithium secondary battery including a positive electrode, a negative electrode for a lithium secondary battery, a separator, and an electrolyte; and activating the lithium secondary battery, wherein the activation includes a high C-rate activation process (high-rate charging), wherein preparing the negative electrode for a lithium secondary battery includes: preparing a negative electrode current collector layer, and forming a first negative electrode active material layer by applying a first negative electrode active material layer composition to one surface or two surfaces of the negative electrode current collector layer using a coater, and forming a second negative electrode active material layer by applying a second negative electrode active material layer composition to the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer using a coater, wherein the first negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and the content of SiOx (x = 0) is 95 parts by weight or more based on 100 parts by weight of the first negative electrode active material, and The second negative electrode active material includes at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride.
13. The method according to claim 12, comprising pre-lithiation of the negative electrode having the first negative electrode active material layer and the second negative electrode active material layer formed on the negative electrode current collector layer, The pre-lithiation of the negative electrode includes a lithium electroplating process, a lithium metal transfer process, a lithium metal deposition process or a stabilized lithium metal powder (SLMP) coating process.
14. The method according to claim 12, wherein forming the second negative active material layer on the first negative active material layer comprises a wet-on-dry process, and The wet-to-dry process comprises: applying the first negative electrode active material layer composition; forming the first negative electrode active material layer by partially or completely drying the applied first negative electrode active material layer composition; and The second negative active material layer composition is applied to the first negative active material layer.
15. The method according to claim 11, wherein forming the second negative electrode active material layer on the first negative electrode active material layer comprises a wet-on-wet process, and The wet-on-wet process comprises: applying the first negative electrode active material layer composition; and The second negative electrode active material layer composition is applied to the first negative electrode active material layer composition in a state where the first negative electrode active material layer composition is not dried.
Citation Information
Patent Citations
Anode for lithium ion battery
JP2009080971A